Tactile-Color System for Accessibility of Color Education: 2.5D UV Printed Supplementary Material for Visually Impaired Students - Shin, Jaeeun; Cho, Jundong; Lee, Sangwon (2021 15th International Conference on Ubiquitous Information Management and Communication (IMCOM), 2021)
Color education materials for visually impaired students are still a lot to be developed due to a lack of materials compared to their needs. In fact, the supplementary materials are essential to teachers at special education schools who teach blind students by using other senses instead of eyesight. However, it has been a lack of support to provide teaching materials for the purpose so far. Since visually impaired people have learned the color concept in an abstract and literary way, they have had problems in understanding the color theory itself. The main purpose of this study is to design the Tactile-Color system using tactile symbols and texture to explain the color theory. This assistive material was produced by 2.5D embossed UV print materials for visually impaired education. The color symbols were designed based on associations between colors and shapes to help people perceive tactile information; they are primary colors (i.e., red, yellow, blue) matching with primary shapes (i.e., circle, triangle, square), respectively. Brightness and saturation in color theory designated to the tactile texture of softness and roughness gradient. The audio guide also supplied to enhance the efficiency of art teachers' classes and to assist the self-learning of visually impaired students. The survey and interviews were conducted with 17 special education teachers for the evaluation of the tactile-color materials. The evaluation results indicate that tactile-color materials can be effective to teach color theory to visually impaired students in the classroom. The positive responses from actual users proved the usefulness and understandability of the Tactile-Color system.